Implementing Islamic Values through Dzikir Fida’ to Foster the Religious Character of the Darussalamah Prayer at Mushola Darussalamah Dusun V Reno Basuki Kecamatan Rumbia - Khusnul Fadilah; Isnaini Nur Azizah; Irhamudin Irhamudin (CV. Creative Tugu Pena, 2025)
This study examines the implementation of Islamic values through dzikir fida’ in fostering the religious character of the congregation at Mushola Darussalamah, Dusun V, Reno Basuki Village, Rumbia District, Central Lampung Regency. Dzikir fida’, as a collective spiritual practice, is identified as an effective medium for strengthening faith, moral conduct, and daily behavior grounded in Islamic values, including i‘tiqādiyyah (creedal), khuluqiyyah (moral), and ‘amaliyyah (practical) dimensions. The research employs a qualitative field approach using purposive sampling. Data were collected through structured interviews, participant observation, and documentation involving dzikir leaders, congregation members, and community figures, with data validity ensured through source triangulation. The findings reveal that dzikir fida’, conducted congregationally every Wednesday night until Thursday with a structured sequence of supplications and the recitation of “lā ilāha illā Allāh” 70,000 times, significantly contributes to the development of religious character. Its impact is reflected in enhanced inner peace, strengthened social solidarity, and increased piety. The influence of the practice is evident across social aspects (reinforcing ukhuwah islāmiyyah), psychological aspects (reducing stress and fostering gratitude), and religious aspects (strengthening faith and discipline in worship). Nevertheless, challenges remain, particularly the limited participation of younger generations, which calls for more intensive outreach and promotion. This study contributes to the discourse on character education rooted in spiritual and cultural traditions and offers recommendations for expanding dzikir fida’ as a moral and spiritual intervention within society.